2023
DOI: 10.1186/s12889-023-15105-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the health impacts of climate change among Canadians

Abstract: Background Understanding public perceptions of the health risks of climate change is critical to inform risk communication and support the adoption of adaptive behaviours. In Canada, very few studies have explored public understandings and perceptions of climate impacts on health. The objective of this study was to address this gap by exploring perceptions of the link between climate change and health. Methods We conducted a survey of Canadians (n … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…sociodemographic differences in the perception of vulnerability or harm from climate change. [15][16][17] Further, findings indicate that both non-Hispanic Black and Hispanic populations perceive climate change as a threat to their health, consistent with current research documenting communities with greater proportions of Black and Hispanic residents are disproportionately burdened by the adverse effects of climate change. 18,19 The current study also found a link between trust in certain health information sources and climate change harm perception, consistent with previous research that found an association between trust in scientists and belief in global warming and climate change in general.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…sociodemographic differences in the perception of vulnerability or harm from climate change. [15][16][17] Further, findings indicate that both non-Hispanic Black and Hispanic populations perceive climate change as a threat to their health, consistent with current research documenting communities with greater proportions of Black and Hispanic residents are disproportionately burdened by the adverse effects of climate change. 18,19 The current study also found a link between trust in certain health information sources and climate change harm perception, consistent with previous research that found an association between trust in scientists and belief in global warming and climate change in general.…”
Section: Discussionsupporting
confidence: 77%
“…These findings add to a growing body of evidence across North America that identify similar sociodemographic differences in the perception of vulnerability or harm from climate change. 15-17 Further, findings indicate that both non-Hispanic Black and Hispanic populations perceive climate change as a threat to their health, consistent with current research documenting communities with greater proportions of Black and Hispanic residents are disproportionately burdened by the adverse effects of climate change. 18,19…”
Section: Discussionsupporting
confidence: 75%
“…The results of all the mentioned studies Casson et al, (2023); Ayanlade et al, (2023); Galanakis (2023); Tam, Chan & Clayton (2023) found the positive association that climate change affects the social well-being of the people of Pakistan.…”
Section: Tam Chan and Clayton 2023mentioning
confidence: 95%
“…It can also lead to increased rates of physical illnesses, which secondarily would be associated with psychological distress. Casson (2023) on the perceptions of the health impacts of climate change among Canadians. The health risks of climate change is critical to inform risk communication and support the adoption of adaptive behaviours in Canada.…”
Section: The Ricardian Approach Modelmentioning
confidence: 99%